1980
DOI: 10.1172/jci109714
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergic Mechanisms for the Effects of Epinephrine on Glucose Production and Clearance in Man

Abstract: A B S T R A C T The present studies were undertaken to assess the adrenergic mechanisms by which epinephrine stimulates glucose production and suppresses glucose clearance in man: epinephrine (50 ng/kg per min) was infused for 180 min alone and during either alpha (phentolamine) or beta (propranolol)-adrenergic blockade in normal subjects under conditions in which plasma insulin, glucagon, and glucose were maintained at comparable levels by infusion of somatostatin (100 ,ug/h), insulin (0.2 mU/kg per min), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
140
3
1

Year Published

1981
1981
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 338 publications
(156 citation statements)
references
References 30 publications
12
140
3
1
Order By: Relevance
“…This is consistent with the dominant role of sympathetic neuronal activation in mediating exerciseinduced increases in renin release. release, a contention borne out by the recent studies of Felig et al 23 Second, Rizza et al 24 showed that the clearance of epinephrine after infusion appears to depend on a 13 mechanism and, thus, epinephrine levels could be increased by competition for a receptor. Our results are compatible with those of other investigations, but until now, no distinction was made between the type of 13-adrenoceptor antagonist used.…”
Section: Renin Releasementioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with the dominant role of sympathetic neuronal activation in mediating exerciseinduced increases in renin release. release, a contention borne out by the recent studies of Felig et al 23 Second, Rizza et al 24 showed that the clearance of epinephrine after infusion appears to depend on a 13 mechanism and, thus, epinephrine levels could be increased by competition for a receptor. Our results are compatible with those of other investigations, but until now, no distinction was made between the type of 13-adrenoceptor antagonist used.…”
Section: Renin Releasementioning
confidence: 99%
“…Further investigations of the metabolic effects of these drugs when given chronically are indicated. 24 hours showed that nifedipine significantly reduced systolic and diastolic blood pressure throughout the day and the night. The variability of blood pressure was not altered by nifedipine therapy.…”
Section: Metabolic Responsesmentioning
confidence: 99%
“…Bernstein et al [2] have pointed out, however, that adrenaline and propranolol could interfere with the ability of insulin to stimulate glucose disposal and/or inhibit hepatic glucose production. Adrenaline increases glucose production, decreases glucose clearance [23], and impairs tissue sensitivity to insulin in man [5]. Propranolol had no effect on insulin mediated glucose metabolism [5].…”
Section: Discussionmentioning
confidence: 99%
“…23 " 29 In fact, acute catecholamine administration determines impaired insulin action 24 -26 through the inhibition of net glycogen synthesis 28 - 29 and through the stimulation of hepatic glucose production. 24 " 26 However, it is also established that reduced sensitivity to ^-receptor stimulation follows the chronic administration of ^-agonists. 34 - 36 Particularly, Scheidegger et al 61 showed a 30% increase in insulin-stimulated glucose uptake after chronic /3-receptor stimulation in healthy volunteers.…”
Section: Sham Wrap Bmentioning
confidence: 99%
“…23 - 29 Particularly, suppression of insulin secretion by catecholamines is mediated through a-adrenergic receptors, 25 whereas in human subjects, the direct effects of catecholamines on periph-eral and hepatic glucose metabolism appear to be mediated largely through /3-adrenergic receptors. 26 Acute /3-adrenergic stimulation results in impaired insulin action, mainly through the decrease in net glycogen deposition (stimulation of glycogen phosphorylase and inhibition of glycogen synthase) and the increase in hepatic glucose output. 23 - 29 However, the effect of the chronic elevation of the plasma catecholamine concentration on insulin action is still controversial.…”
mentioning
confidence: 99%